KOMUNIKASI PERSUASI ORANG TUA DENGAN ANAK DALAM MEMBENTUK PERILAKU TAAT BERIBADAH DI DESA BANDAR KLIPPA KECAMATAN PERCUT SEITUAN - Fadhilah Balqis Zain (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
this study aims to find out the persuasive communication of parents towards children in shaping the behavior of devout worship in bandar Klippa Percut Sei Tuan village? and What obstacles are faced by parents in shaping the behavior of Taat worship in bandar Klippa Percut Sei Tuan village? The method used in this study was to use a skin method with a case study approach in Bandar Klippa village, Persut Seituan District. The result of this study is that parents are an environment that is very strongly influential on children, in this environment children know various educations and one of them is parental guidance. The role and function of parents have a major influence on the personality and character development of children. The obstacles faced by the master in shaping the behavior of devout worship are firstly too busy in making a living or work and not being able to control or guide the child such as the five-time prayer, both parents do not understand or there is no science in the field of religion.